KAJIAN POTENSI DAN PENGELOLAAN BERKELANJUTAN EKOSISTEM MANGROVE PULAU PANNIKIANG, KABUPATEN BARRU, SULAWESI SELATAN - Rusdi, Rismawaty; Setyobudiandi, Isdrajad; Damar, Ario (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
The best planning and management can be fulfilled if complete and accurate information is available. This research generally aims to examine the potential of mangrove ecosystems on Pannikiang Island in terms of ecological conditions and economic value to assess sustainability status and determine mangrove ecosystem management recommendations. Ecological data collection was carried out by observation, interviews with purposive sampling method, and literature review. Ecological analysis used an important value index, economic analysis used consumer surplus, replacement cost, contingent value, and sustainability analysis used a modification of Rapid Appraisal for Fisheries (RAPFISH) software. The mangrove species that identified were Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorrhiza, Bruguiera sexangula, Ceriops tagal, Sonneratia alba, Xylocarpus granatum, Xylocarpus moluccensis, Aegiceras corniculatum, Lumnitzera racemosa and Avicennia marina. The results analysis of the total economic value of mangrove ecosystem on Pannikiang Island with an area obout 86.31 ha was Rp5.050.275.373,00 /year or an average was Rp58.513.212,00 /ha/year. The sustainability status of the mangrove ecosystem on Pannikiang Island based on multidimensional analysis is still relatively unsustainable. Therefore, some strategy recommendations are rehabilitation of mangrove vegetation; controlling the utilization of mangrove ecosystems carried out by community, especially exploitative uses; involve community in mangrove ecosystems management; make formal regulation related to management of mangrove ecosystems.